EMPLOYEE ENGAGEMENT IN STARTUPS navigating growth, culture, and innovation. - Rossides, Nicos (ROUTLEDGE, 2026)
The relentless pace, the challenge of the untried, the dive into the unknown-this is the startup world. It converges with the deep human needs for mastery, growth, and meaning.This book explores that crucial intersection. Unlike other books on employee engagement, this one is written specifically for the startup environment. It combines lessons learned from years leading businesses, direct experience with innovative startups, and insights from the latest research on both engagement and entrepreneurship. Discover clear, workable strategies to navigate keeping your team engaged throughout your startup's journey.This book is a vital resource for students, academics, and professionals alike who need proven ways to build connected, high-performing startup teams.
Keywords: Employee motivation.; New business enterprises -- Management.; elektronické knihy; electronic books